2017
DOI: 10.2196/resprot.6806
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Hypofractionated Radiotherapy and Chemotherapy in High-Grade Extremity Soft Tissue Sarcomas: Phase 2 Clinical Trial Protocol

Abstract: BackgroundNeoadjuvant radiotherapy (RT) and chemotherapy are applied to large, high-grade extremity soft tissue sarcomas to treat metastatic disease earlier and sterilize margins to perform R0 surgery. However, preoperative RT increases wound complication rates (rWC), delaying adjuvant chemotherapy or preventing it from being administered altogether. Hypofractionated neoadjuvant RT can be offered in this situation, concomitant to chemotherapy, allowing patients to receive chemotherapy as a preoperative treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…The literature presents RR cell lines generated by using different irradiation schemes [6,9,[27][28][29][30][31][32]. Herein, we took inspiration from the hypo-fractionated program used for sarcoma patients, irradiating cells with 6 Gy 6 times [18] that, considering the low α/β ratio of RMS [20], permit us to reach radiobiologically equivalent dose of 66 Gy, equal to that clinically delivered with conventional schedule [2]. It should be noted that fractions were not delivered daily but when cells restarted to growth, as used in other studies [9,27] that consider tumor cells in 2D more sensitive to treatments [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature presents RR cell lines generated by using different irradiation schemes [6,9,[27][28][29][30][31][32]. Herein, we took inspiration from the hypo-fractionated program used for sarcoma patients, irradiating cells with 6 Gy 6 times [18] that, considering the low α/β ratio of RMS [20], permit us to reach radiobiologically equivalent dose of 66 Gy, equal to that clinically delivered with conventional schedule [2]. It should be noted that fractions were not delivered daily but when cells restarted to growth, as used in other studies [9,27] that consider tumor cells in 2D more sensitive to treatments [15].…”
Section: Discussionmentioning
confidence: 99%
“…RT for RMS tumors usually provides 50/66 Gy in fractions of 2 Gy [2]. However, hypofractioned programs, single higher doses for a reduced number of fractions, are used to overcome the intrinsic radioresistance of RMS [18]. In order to generate clinically relevant radioresistant (RR) RMS cell lines, RD and RH30 cells were subjected to hypo-fractionated schedule based on the use of 6 fractions, each at 6 Gy.…”
Section: Development and Onco-phenotypic Characterization Of Clinicalmentioning
confidence: 99%
“…However, there are extensive disputes and challenges regarding the use of chemotherapy and radiotherapy in these patients. Some studies have adopted optional chemotherapy treatment as an adjunct to increase the chance of preserving a limb, but the use of this method has not had a significant effect on overall survival [4].…”
Section: Mini Reviewmentioning
confidence: 99%
“…Other studies have suggested that in patients for whom the tumor cannot be removed completely by surgery, to increase the chance of tumor necrosis considering its high survival, a neoadjuvant chemotherapy treatment with hypofractionated radiotherapy or in some cases adjuvant chemotherapy, depending on the living cells, has been recommended. These methods have been able to improve patient complications and induce a pathologic response [4]. Various protocols have been proposed for radiotherapy of these patients.…”
Section: Mini Reviewmentioning
confidence: 99%
“… 13 25 Gy in 5 fractions in combination with chemotherapy has been reported as a phase 2 trial protocol. 14 The advantage for geriatric patients is the significantly reduced overall treatment time and the limited daily visits to the radiation oncology department making it more feasible as an outpatient treatment. Thus, radiotherapy is an option even in frail geriatric patients who otherwise would undergo surgery alone due to the high burden of daily visits to radiation treatment units over several weeks.…”
Section: Introductionmentioning
confidence: 99%